等尺性収縮による舌挙上運動と舌骨上筋群筋活動の関係 - 福岡 達之; 吉川 直子; 川阪 尚子; 野崎 園子; 寺山 修史; 福田 能啓; 道免 和久 (jibi to rinsho, 2010)
The present study examines the utility of isometric lingual exercise as a means of strengthening the suprahyoid muscles in 10 healthy volunteers (mean age, 27.4 years ; range, 23-34 years). We measured the maximum tongue pressure of each subject using the Iowa Oral Performance Instrument (IOPI). We then measured the electromyographic activity of the suprahyoid muscles during a tongue press with a load intensity of 20%, 40%, 60% and 80% of maximum tongue pressure while providing feedback about the tongue pressure on a monitor. We also compared the electromyographic activity of the suprahyoid muscles during the tongue press using maximum tongue pressure, the head lift exercise, the Mendelsohn maneuver and tongue protrusion. Increasing tongue pressure resulted in increased electromyographic activity of the suprahyoid muscles, and the magnitude of the resultant electromyographic activity differed significantly with each load. Among the various training movements, lingual exercise with maximum tongue pressure maximally increased the electromyographic activity of the suprahyoid muscles. These results indicate that isometric lingual exercise is a useful method for strengthening the suprahyoid muscles. 本研究の目的は、舌骨上筋群に対する筋力トレーニングの方法として、等尺性収縮による舌挙上運動の有用性を検討することである。対象は健常成人 10 名 (平均年齢 27.4 ± 3.8歳)、方法は各対象者の最大舌圧を測定した後、最大舌圧の 20％、40％、60％、80％の負荷強度で舌を挙上させた時の舌骨上筋群筋活動を表面筋電図で記録した。さらに、最大舌圧で舌を挙上させた時と頭部挙上、Mendelsohn 手技、挺舌について、各動作時の舌骨上筋群筋活動を記録した。舌骨上筋群筋活動は最大舌圧時の値を 100％として正規化し％RMS を用いて比較した。結果から、舌圧が上昇するに従い舌骨上筋群筋活動も増大を示し各強度で有意差を認めた。種々のトレーニング動作の比較では、最大舌圧による舌挙上時の舌骨上筋群筋活動が最も高く、頭部挙上 (34.8 ± 15.6％)、Mendelsohn 手技 (42.5 ± 14.8％)、挺舌 (43.0 ± 16.4％) と比べて有意差を認めた。以上より、等尺性収縮による舌挙上運動が、舌骨上筋群に対する筋力トレーニングの方法として有用となる可能性が示唆された。